Fucosylated Antigens in Cancer: An Alliance toward Tumor Progression, Metastasis, and Resistance to Chemotherapy - Blanas, Athanasios; Sahasrabudhe, Neha M.; Rodríguez, Ernesto; van Kooyk, Yvette; van Vliet, Sandra J. (Frontiers in Oncology, 2018)
Aberrant glycosylation of tumor cells is recognized as a universal hallmark of cancer pathogenesis. Overexpression of fucosylated epitopes, like type I (H1, Lewisa, Lewisb, sialyl Lewisa) and type II (H2, Lewisx, Lewisy, sialyl Lewisx) Lewis antigens frequently occurs on the cancer cell surface and is mainly attributed to upregulated expression of pertinent fucosyltransferases (FUTs). Nevertheless, the impact of fucose-containing moieties on tumor cell biology is not fully elucidated yet. Here we review the relevance of tumor-overexpressed FUTs and their respective synthesized Lewis determinants in critical aspects associated with cancer progression, such as increased cell-survival and proliferation, tissue invasion and metastasis, endothelial to mesenchymal transition, endothelial and immune cell interaction, angiogenesis, multi-drug resistance and cancer stemness. Furthermore, we discuss the potential use of enhanced levels of fucosylation as glycan biomarkers for early prognosis, diagnosis and disease monitoring in cancer patients.